Strategy for engineering learning based on educational and competitive robotics: case study at Universitaria de Investigación y Desarrollo, UDI - Zabala Vargas, Sergio Andrés; Pérez López, Jhon Albert; Rodríguez Hernández, Henry Fernando (Ingeniería Solidaria, 2014)
In the context of developing engineering skills across the full spectrum of the discipline, methodologies, tools, strategies and experiments have been implemented over the years to consolidate these kills in students finishing in the final stages of their university studies. The project in this paper is presented against this background, and consists of the developement of a pilot program to incorporate information and communication technology (ICT) into the curriculum, resulting in a clear strategy of innovation for education. It was of Bucaramanga, and for electrical engineering students at the students -as well as academic requirements and their productive enviroment - robotics, and specifacally competitive robotics, have been used to simulate modeling, desing and product implementation skills. This work has allowed the incorporation of an integrating strategy in which students carry out different stages of engineering projects: 1. Analysis of the challenge set, 2) The mechanical design of a device, generally moving, 3) The electronic stage, including control and direct manipulation of actuators; with these elements it is possible to create, 4) A competitive prototype that can be validated to provide feedback data and propose strategies of continuos improvement